KEWENANGAN PEMERINTAH PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA DALAM REVITALISASI PEMBANGUNAN TAMAN TEBET ECO PARK: The Authority of the Provincial Government of the Special Capital Region of Jakarta in the Revitalization of Tebet Eco Park Development - Artha Noviyantri Utami; Dhany Rahmawan (Faculty of Law, Universitas Trisakti, 2025)
This research analyzes the authority of the DKI Jakarta Provincial Government in the revitalization of Tebet Eco Park. The project has been approved by the Governor of DKI Jakarta with a budget of 40 billion for the construction of fencing, installation of bridge sensors, and construction of a plaza equipped with public facilities. This research aims to understand the relationship between the central and local governments in the revitalization authority based on regional autonomy and the principles of local government. The research method used is normative juridical with descriptive nature, using secondary data and interviews, as well as qualitative analysis and deductive inference. The results and the conclusion showed that the authority of the DKI Jakarta Provincial Government is in accordance with the 1945 Constitution Article 18 paragraph (2), Law No. 23 of 2014, Law No. 29 of 2007, and PP No. 18 of 2016, which includes the legitimacy of revitalization from planning to management. The DKI Jakarta Provincial Government has also carried out revitalization supervision according to its authority even though the implementation is by a third party.